BURNOUT AND PRE-COMPETITION: A STUDY OF ITS OCCURRENCE IN BRAZILIAN SOCCER PLAYERS - Lopes Verardi, Carlos E. [UNESP]; Nagamine, Kazuo Kawano; Micelli Domingos, Neide A.; De Marco, Ademir; Cristina De Oliveira Santos Miyazaki, M. (Univ Illes Balears, 2015)
The objective of this study was to identify and interpret the occurrence of symptoms associated with the burnout syndrome during the pre-competition phase. A total of 134 male soccer players participated in the study: 71 professionals (M-age = 22.77 +/- 3.98 years) and 63 amateurs (M-age = 17.18 +/- 0.84 years) from three teams participating in the Sao Paulo State Championship, Series A-1 and A-2 (professional category) and the Sao Paulo Junior Soccer Cup (amateur category), organized by the Sao Paulo Soccer Federation, State of Sao Paulo, Brazil. In order to evaluate the Burnout Syndrome, a version of the Athlete Burnout Questionnaire (ABQ) was used, an instrument developed especially for the assessment of burnout in athletes. Values associated with greater vulnerability and, consequently, greater risk of evolving to the syndrome, were observed in a small portion of the players interviewed. The impact represented by the players with higher scores for burnout and the importance of such in relation to the team should be investigated.
Keywords: Burnout; Soccer; Professionals; Amateurs